Nigerian Expatriates' Integration in Host Countries and its Implication for Nigeria's Foreign Policy Agenda - Ameen, Abdulkadir; Arowona, Abdulazeez Lekan; Abdulquadir, Abdulazeez (Journal of Contemporary International Relations and Diplomacy, 2024)
This paper seeks to analyse the challenges faced by Nigerian expatriates in the quest to get integrated in their host countries and the implications it has on Nigeria’s foreign policy agenda. The problem arises due to the increasing mobility of Nigerian expatriates abroad, challenges faced by them and potential impacts such an increasing mobility bears for the international standing and strategic interests of Nigeria. The broad objective is to examine the effects that integration of Nigerian expatriates has on the implementation of foreign policy objectives of Nigeria. The study uses primary data gathered from random sampling through Google form sent to a famous Nigerian in Diaspora (NIDO)’s WhatsApp group. Also, secondary data from the literature, including academic journals, books, newspapers, and historical accounts, were used. The major findings of study are: that the Nigerian expatriates’ integration is hampered by a range of issues like xenophobia and legal restrictions on access to critical socio-economic activities needed for effective engagement in diplomacy. The study offers, among other recommendations, increased institutional support for diaspora engagement to break legal and socio-economic barriers, partnership with the host governments and organizations that can aid maximum integration in the host countries. These can be achieved through cultural exchange and educational programs put in place under citizens diplomacy to ensure that there is maximum utilization of Nigerian experts for the development of foreign policy agenda of the country.